"Authentic Warmth in These Uncertain Times": The Impact of Authenticity in COVID-19 Advertising on Brand Warmth and Consumer Responses. Issue 2 (17th February 2023) - Yang, Jing; Jiang, Mengtian (Montina); Kim, Taeyoung
Abstract: This study investigated the impact of the perceived authenticity of brands' COVID-19 advertisements on consumers' perception of brand warmth and the subsequent responses on brand attitude and engagement intention. An online survey was used to acquire consumers' evaluations of COVID-19 video ads published between March and August in 2020. Results showed that the message authenticity significantly increased consumers' perception of brand warmth, brand attitude, and engagement intention. Furthermore, the serial mediation results revealed the underlying mechanism that authentic ads evoked positively valenced emotional responses, which increased perceived brand warmth and further resulted in positive brand attitudes and engagement intentions. Practical implications and theoretical advancement are also discussed.